Polynomial-Time Solution to the Hidden Subgroup Problem for a Class of Non-abelian Groups - Roetteler, Martin; Beth, Thomas (1998)
We present a family of non-abelian groups for which the hidden subgroup problem can be solved efficiently on a quantum computer.